Rethinking Titu Cusi Yupanqui’s Negotiations with Spanish Peru for Vilcabamba’s Surrender - Gillen, Ryan Edward (My University, 2013)
In the sixteenth century, the penultimate ruler of the Inca dynasty, Titu Cusi Yupanqui, wrote his account of the Spanish conquest. An Inca Account of the Conquest of Peru has been hailed by historians as crucial to the understanding of the period because it was an indigenous recount of Spain's conquest yet has not been examined as what it truly is: Titu Cusi's own attempt to renegotiate himself back into the power structure of Tahuantinsuyu. This paper serves as a challenge to the current historiography on Titu Cusi's relación that questions the sincerity of the Inca's negotiations on the grounds that they were merely an attempt to stall in order to preserve the Neo-Incan state of Vilcabamba's independence. That incorrect historiography’s portrayal of negotiations as a stall contains a fatalistic view of the Inca state of Vilcabamba; previous historians have seen Spanish conquest as inevitable. Instead, the negotiations must be seen as an attempt to manipulate Spanish authorities to maximize the return for Titu Cusi, politically, socially, and economically. Titu Cusi needed to use both Spanish allies and Spanish scapegoats in order to absolve himself and his father, Manco Inca, of rebelling against the Crown of Castile. The Inca manipulated Spanish concepts of nobility, religion, and descent in order to achieve his ends
Keywords: Titu Cusi Yupanqui; Inca; Vilcabamba; Conquistidors; South America--Peru--Spanish Conquests; Spain--New World--Catholicism; Inca--History; Peru--History; South America--Peru; Cuzco; Martin de Pando; Manco Inca Yupanqui; Tupac Amaru